Social Isolation: How Can the Effects on the Cholinergic System Be Isolated? - Myslivecek, Jaromir (Frontiers in Pharmacology, 2021)
Social species form organizations supporting individuals because the consequent social behaviors help these organisms survive. The isolation of such individuals can be considered a stressor. Here, we review potential mechanisms by which social isolation affects cholinergic signaling and vice versa and how changes in cholinergic signaling affect the changes due to social isolation. However, there are two important problems that one may encounter in this topic. First, one should be aware that isolation schemes differ in their duration (1-165 days) and beginning (immediately after birth to adulthood). Second, there is an important problem that is usually not considered when studying the role of the cholinergic system in neurobehavioral correlates—muscarinic and nicotinic receptor subtypes do not differ sufficiently in their affinity for agonists and antagonists. Moreover, some potential cholinesterase inhibitors also affect other targets, such as receptors or other neurotransmitter systems. Thus, the role of the cholinergic system in social isolation should be carefully considered, and one should keep in mind that multiple receptor systems could be involved in the respective central nervous system response.